2009
DOI: 10.1080/19942060.2009.11015265
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of Low Speed Axial Flow Compressor Rotors with Sweep and Tip Clearance

Abstract: Blade tip gap, though finite, has great influence on the performance of a turbomachine. Tilting the blade sections to the flow direction (blade sweep) would increase the operating range of an axial compressor by modifying the pressure and velocity fields on the suction surface. The present paper investigates the combined effect of these two factors on various flow characteristics in a low speed axial flow compressor. For the present study, six computational domains were modeled: two rotor sweep configurations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Finally, validation-calibration of CFD codes for predicting the extremely challenging areas of separated flows can be also carried out (Pachidis et al, 2006). The increased computational power available nowadays throughout the research community has increased the application of high-fidelity numerical approaches on every kind of flow prediction, starting from pure aerodynamic phenomena occurring at inlets or compressors and extending them in combustion or turbine cooling research, employing multidisciplinary tools of chemical or heat transfer nature (Chaluvadi et al, 2003;Ramakrishna et al, 2009;Ummiti et al, 2009). In case of far off-design turbomachinery performance studies such as the above-described ones, the availability of experimental datasets is the only aspect that prevents the numerical tools from being further validated and at a second stage further improved.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, validation-calibration of CFD codes for predicting the extremely challenging areas of separated flows can be also carried out (Pachidis et al, 2006). The increased computational power available nowadays throughout the research community has increased the application of high-fidelity numerical approaches on every kind of flow prediction, starting from pure aerodynamic phenomena occurring at inlets or compressors and extending them in combustion or turbine cooling research, employing multidisciplinary tools of chemical or heat transfer nature (Chaluvadi et al, 2003;Ramakrishna et al, 2009;Ummiti et al, 2009). In case of far off-design turbomachinery performance studies such as the above-described ones, the availability of experimental datasets is the only aspect that prevents the numerical tools from being further validated and at a second stage further improved.…”
Section: Introductionmentioning
confidence: 99%
“…The Fig. 4 Flow domain with the given boundary conditions results obtained with these two turbulence models were compared with the available experimental results (given in reference [17]). Grid independency study was also conducted and the mesh size was optimized to about 700 000 mesh elements for the rotor and 450 000 elements for the stator.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Grid independency study was also conducted and the mesh size was optimized to about 700 000 mesh elements for the rotor and 450 000 elements for the stator. Details of the mesh, grid independence study, wall function treatment and y+ pertaining to the present study can be found in Ramakrishna and Govardhan [17]. Details of the flow domain with the given boundary conditions are shown in Fig.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Details of the computational methodology adopted in the present work, numerical validation and so forth, have been presented in Ref. [17][18][19] in detail; and will not be repeated here. High quality hexahedral grids have been employed in the computations.…”
Section: The Computational Modelmentioning
confidence: 99%